2021
DOI: 10.1177/0143034321998741
|View full text |Cite
|
Sign up to set email alerts
|

Depression symptoms as a mediator between social support, non-suicidal self-injury, and suicidal ideation among Arab adolescents in Israel

Abstract: The purpose of the current study was to explore whether depression symptoms mediate the relationships between perceptions of social support from three sources; namely parents, teachers, and peers, and non-suicidal self-injury (NSSI) and suicidal ideation. We also tested the interactions between the different sources of support. Focusing on the Arab-Israeli population is unique as it is an ethnic minority characterized with strong familial support, and less access to mental health services compared to the ethni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 95 publications
1
1
0
Order By: Relevance
“…First, despite the expectation of higher psychological distress among Palestinian adolescents due to their status as an ethnic minority, our study participants reported low levels of psychological distress. This aligns with previous studies (Berger et al, 2020; Madjar et al, 2021) and prompts consideration of the tools employed. It is plausible that the tools, such as the GHQ-12, may lack cultural validity to effectively capture the nuances of psychological distress within the Palestinian minority context.…”
Section: Discussionsupporting
confidence: 87%
“…First, despite the expectation of higher psychological distress among Palestinian adolescents due to their status as an ethnic minority, our study participants reported low levels of psychological distress. This aligns with previous studies (Berger et al, 2020; Madjar et al, 2021) and prompts consideration of the tools employed. It is plausible that the tools, such as the GHQ-12, may lack cultural validity to effectively capture the nuances of psychological distress within the Palestinian minority context.…”
Section: Discussionsupporting
confidence: 87%
“…For example, a previous study found that the quality of peer connections is strongly associated with children's internalizing difficulties ( 44 ), which are, in turn, positively associated with NSSI behaviors ( 13 ). Furthermore, adolescents who feel supported by their teachers are less likely to engage in NSSI behavior ( 45 47 ).…”
Section: Introductionmentioning
confidence: 99%